Dati sulla vegetazione dell'isola di Saseno - Hoda P.; Mersinllari M. (La cooperazione italo-albanese per la valorizzazione della biodiversità, 2000)
Sazani is the only island in Albania. It has a typical Mediterranean climate and vegetation. The most important vegetation types of the island are analysed. These Mediterranean communities are: Orno-Quercetum ilicis Horvatic 1958, Orno-Quercetum cocciferae Horvatic 1958, Salvio-Phlometum fruticosa Barbagallo, Brullo & Fagotto 1979, Oleo-Lentiscetum Molinier 1954 var. adriaticum Trinajtsic 1977, Oleo-Euphorbietum dendroidis Trinajstic (1973) 1984, Pistacio-Pinetum halepensis De Marco et al. 1984, Ericetum manipuliflorae Oberdorfer 1954, Brachypodietum ramosi, Crithmo-Limonietum andracti Mullaj 1989. A phytosociological table is given.
Seminario: La Cooperazione Italo-Albanese per la Valorizzazione della Biodiversità, 2000/02/24-26, Lecce (Italy)